Welcoming the life of society 5.0 in Indonesian education using soft system methodology - Arif Bagas Adi Satria (IAIN Salatiga, 2021)
Commemorate the life of Society 5.0 cannot separate from utilization of the latest digital technology. Advanced the education of Indonesia is the duty of the people to become Indonesian nation, that is to enrich the life of the nation. The Education of Indonesia, which has been using for the stream of Western Education namely the class style (bank style), emphasizes tables, chairs and blackboards. We must replace with a more flexible style of education and millennial oriented, no longer rely on an old-fashioned educational methods. Therefore, we need an effort in welcoming life of Society 5.0 with Soft System Methodology utilization. The method used in this study is a descriptive qualitative analysis method with secondary data to describe the phenomena that occur in the field with sufficient and supporting data for this paper. Based on the studies that have carried out, we can conclude that the proper use of the Soft System Methodology can advance Indonesian Education to Welcoming the Society 5.0.